2020
DOI: 10.1371/journal.pone.0230066
|View full text |Cite
|
Sign up to set email alerts
|

Lack of transmission of Sugarcane yellow leaf virus in Florida from Columbus grass and sugarcane to sugarcane with aphids or mites

Abstract: Sugarcane yellow leaf virus (SCYLV), the causal agent of yellow leaf disease, naturally infects at least three plant species in Florida: sugarcane (Saccharum spp.), the weed Columbus grass (Sorghum almum) and cultivated sorghum (S. bicolor). All three hosts are also colonized by the sugarcane aphid (Melanaphis sacchari), the main vector of SCYLV worldwide. To understand the high incidence of SCYLV observed in sugarcane commercial fields and in germplasm collections, we investigated the transmission efficiency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 36 publications
(58 reference statements)
0
5
0
Order By: Relevance
“…Although our sampling plan was not designed to test host plant preference, the difference of preference between the two species appears obvious. The results of Boukari et al [ 38 ] obtained in Florida confirm this preference, showing that sugarcane harbors almost only M . sacchari (COI haplotypes H2 and H3), which is absent from aphids on Sorghum spp.…”
Section: Discussionmentioning
confidence: 65%
“…Although our sampling plan was not designed to test host plant preference, the difference of preference between the two species appears obvious. The results of Boukari et al [ 38 ] obtained in Florida confirm this preference, showing that sugarcane harbors almost only M . sacchari (COI haplotypes H2 and H3), which is absent from aphids on Sorghum spp.…”
Section: Discussionmentioning
confidence: 65%
“…Recently, three inherently dissimilar haplotypes of M. sacchhari were reported from United States including haplotype one (H1) infecting Sorghum species and sugarcane whereas, H3 haplotype known to occur on sugarcane, sorghum and Johnsongrass (S. halepense) and H6 haplotype colonizes both sugarcane and Johnsongrass (Nibouche et al, 2018). Moreover, from Florida, lack of efficient transmission of SCYLV from sugarcane and Columbus grass to sugarcane has been shown by M. sacchari and mites (Oligonychus grypus), suggesting the SCYLV vector needs further identification (Boukari et al, 2020).…”
Section: Mechanism Of Virus-vector Interactionmentioning
confidence: 99%
“…As SCYLV is one of the causal pathogens of YLD, recently, Boukari et al (2020) investigated the transmission efficiency of SCYLV by aphid (Melanaphis sacchari) on YLD susceptible sugarcane cultivar CP96-1252 and the inoculated plants were found negative for the presence of SCYLV by tissue blot immunoassay (TBIA) and reverse transcription polymerase chain reaction (RT-PCR). The results revealed that the M. sacchari is one of the prominent vector of SCYLV in different parts of the world but it is not a vector of SCYLV in Florida.…”
Section: Resultsmentioning
confidence: 99%